Penilaian Petani Terhadap Kinerja Penyuluh Pertanian (Studi Kasus di Kelurahan Bonto Manai, Kecamatan Bissamppu Kabupaten Bantaeng) - Amruddin Amruddin; Nurdin Nurdin; Ahmad Syafii (Jurnal Agribis, 2022)
The purpose of this research; 1) to determine the performance of agricultural extension workers in Bonto Manai Village, Bissappu District, Bantaeng Regency, and 2) to determine the farmer's assessment of the performance of agricultural extension workers in Bonto Manai Village, Bissappu District, Bantaeng Regency. This research took place in October-December 2017. The population of this study were all farmers in Bonto Manai Village, Bissappu District as many as 185 people. The sample of this study was taken by 10% of the existing population as many as 20 rice farmers. The performance of agricultural extension workers in Bonto Manai Village, Bissappu District, Bantaeng Regency, namely, a) The main activities of agricultural extension, b) Creating agricultural extension programs, c) Selecting and applying agricultural extension methods, d) Carrying out self-help and farmer-initiated development, f) Developing areas, and g) Develop cooperative relations with agricultural extension workers. Based on the analysis of farmers' assessment of the performance of agricultural extension workers in Bonto Manai Village, Bissappu District, Bantaeng Regency, the analysis results show that; a) The main activities of agricultural extension, stating Satisfied 55%, Quite Satisfied 30%, Dissatisfied 15%, b) Providing agricultural extension planning data, stating Satisfied 65%, Sufficiently Satisfied 25%, Dissatisfied 10%, c) Making agricultural extension program, stating Satisfied 50%, Sufficiently Satisfied 40%, Dissatisfied 10%, d) Preparation of agricultural extension materials, stating Satisfied 65%, Sufficiently Satisfied 35%, Dissatisfied 0%, e) Application of extension methods, which stating Satisfied 75%, Sufficiently Satisfied 20%, Not Satisfied 5%, f) Carrying out self-help and self-help development of farmers, stating Satisfied 80%, Sufficiently Satisfied 5%, Dissatisfied 3 15%, g) Regional development, stating Satisfied 70 %, Sufficiently Satisfied 20%, Not Satisfied 10%, and h) Cooperation relationship with agricultural extension workers, which states that they are 95% Satisfied, 5% Satisfied, and 0% Dissatisfied.